Effects of a long‐term anoxic warming scenario on microbial community structure and functional potential of permafrost‐affected soil. (9th September 2021) - Yang, Sizhong; Liebner, Susanne; Walz, Josefine; Knoblauch, Christian; Bornemann, Till L. V.; Probst, Alexander J.; Wagner, Dirk; Jetten, Mike S. M.; in 't Zandt, Michiel H.
Abstract: Permafrost (PF)‐affected soils are widespread in the Arctic and store about half the global soil organic carbon. This large carbon pool becomes vulnerable to microbial decomposition through PF warming and deepening of the seasonal thaw layer (active layer [AL]). Here we combined greenhouse gas (GHG) production rate measurements with a metagenome‐based assessment of the microbial taxonomic and metabolic potential before and after 5 years of incubation under anoxic conditions at a constant temperature of 4°C in the AL, PF transition layer, and intact PF. Warming led to a rapid initial release of CO2 and, to a lesser extent, CH4 in all layers. After the initial pulse, especially in CO2 production, GHG production rates declined and conditions became more methanogenic. Functional gene‐based analyses indicated a decrease in carbon‐ and nitrogen‐cycling genes and a community shift to the degradation of less‐labile organic matter. This study reveals low but continuous GHG production in long‐term warming scenarios, which coincides with a decrease in the relative abundance of major metabolic pathway genes and an increase in carbohydrate‐active enzyme classes.